Status of biochemical content in papaya (Carica papaya L.) after post-harvest pathogenesis by fungi - Rathod, Gulab; Chavan, Ashok M (Current Botany, 2012)
Post-harvest fungi depleted the pectin, sugar, ash, phosphorous, calcium and ascorbic acid content of papaya fruit.